Risk factors leading to peptic ulcer disease: systematic review in literature - M. Asali, Aghareed; Alghamdi, Mohammed A.; Fallatah, Sumayah A.; Alholaily, Walaa A.; Aldandan, Raja G.; Alnosair, Alaa H.; AlKhars, Ali A.; Alreheli, Moroj F.; Almohaini, Mohammad O.; Alharbi, Rawabi A. (International Journal Of Community Medicine And Public Health, 2018)
This review is aiming to discuss the risk factors which lead to the occurrence of PUD during the period from July 2018 to August 2018. The present review was conducted by searching in Medline, Embase, Web of Science, Science Direct, BMJ journal and Google Scholar for, researches, review articles and reports, published over the past years. Books published on peptic ulcers and on the pathogenesis of human disease were also included., were searched up to August 2018 for published and unpublished studies and without language restrictions, the selected studies were summarized and un reproducible studies were excluded. If several studies had similar findings, we randomly selected one or two to avoid repetitive results. On the basis of findings and results this review found the H. Pylori and the use of NSAIDs are the most common risk factors for developing PUD, and also the genetic, stress and comorbidity increase the risk of PUD occurrence so successful eradication and prevention of the risk factors should be conducted to prevent the presence of PUD and is complication.